Definition of psoriasis severity. (3rd December 2018) - Augustin, M.; Langenbruch, A.; Gutknecht, M.; Reich, K.; Körber, A.; Maaßen, D.; Mrowietz, U.; Thaçi, D.; von Kiedrowski, R.; Radtke, M.A.
Summary: Measurement of the severity of a patient's psoriasis is very important, for a variety of reasons. For example, it allows doctors to select the right level of treatment, to then see how well treatments are working, and it allows researchers to compare different treatments on similar patients. Some treatments called systemic treatments, which work on the whole body rather than just the skin, are only available to patients with 'moderate to severe' disease. Measurement of psoriasis severity is generally based on two different scoring systems: the Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI). PASI is used to record the redness, thickness and scaling of a patient's psoriasis and to measure how well a treatment works, as a reduction in the PASI score means a reduction in these symptoms. DLQI consists of 10 questions concerning a dermatology patient's perception of the impact of their skin disease on different aspects of their quality of life (QoL) over the last week, including symptoms and feelings, daily activities, leisure, work or school, personal relationships and the side effects of treatment. Higher scores indicate greater impairment of QoL. However, not all guidelines give the same advice on how to combine the results of DLQI and PASI; for example, some say that a score of >10 for both DLQI and PASI suggests moderate‐to‐severe psoriasis, while others say a score of >10 for DLQI or PASI suggests moderate‐to‐severe psoriasis. In this study from Germany, data from 3274 patients were analysed for disease severity based on PASI and DLQI together or separately. The proportion of patients with PASI and DLQI >10 was 14.0%, although 45.3% attained at least PASI or DLQI >10. The authors therefore propose an international standardization for the sake of more reliable treatment and healthcare planning. Abstract : Linked Article:  Augustin et al. Br J Dermatol 2018;179 :1385–1391